Monitoring of the transmission line galloping with a novel distributed optical fibre sensor and its statistical data analysis. Issue 1 (4th December 2019) - Wu, Huijuan; Tang, Bo; Xiao, Yao; Qiu, Haoyu; Zheng, Yi; Rao, Yunjiang
Abstract : The wind‐induced galloping of the overhead transmission line threatens safety and serviceability of the power systems. In this study, a novel distributed optical fibre sensor system based on the polarisation‐sensitive optical time‐domain reflectometry technology is proposed, which can monitor the long‐distance transmission line of over dozens of kilometres online in full scale by measuring its accompanying overhead ground wire grounding wire. Also it has good ability for surviving in harsh environments and easy maintenance. To meet the needs of long‐distance monitoring, an equalisation processing method is used to reduce the influence of signal attenuation with the fibre length extension. In the continuous time–space statistics, adaptive galloping signal detection and the galloping level division of wind‐induced disturbances are realised through the boxplot method; and in the continuous frequency–space statistics, the galloping frequency distribution along the cable is analysed simultaneously. Through the time–space and the frequency–space statistics upon the big data, the abnormal galloping moments and locations can be determined automatically in real time.